Fertigation with micronized Sulfur rapidly reduces soil pH - Almutairi, Khalid (2013)
Blueberry is adapted to low soil pH in the range of 4-5.5. At higher pH, soil is often modified with elemental sulfur (S) prior to planting. A 2-year study was conducted to determine the potential of applying micronized wettable S by fertigation through the drip system to reduce soil pH in highbush blueberry. The field was planted in October 2010. The S was mixed with water and injected weekly for 2 months prior to planting and each fall after planting (2011 and 2012), at rates of 0, 50, 100 and 150 kg/ha per year, and was compared to the standard practice of incorporating granular S into the soil prior to planting (two applications of 800 kg/ha each). Sulfur fertigation quickly reduced soil pH (0-10 cm) within a month from 6.6 with no S to 5.8 with 100-150 kg/ha S, but the change was short-term and by December averaged 6.2 and 6.0, respectively. Conventional granular S, in comparison, averaged 6.4 on the first date and 6.1 on the second. In July the following year, soil pH ranged from 6.5 with no S to 6.1 with 150 kg/ha and averaged 6.0 with granular S. Soil pH remained relatively constant thereafter with S fertigation but continued to decline to levels as low as 4.7 with granular S. The treatments had no effect on winter pruning weight in year 1 or on total plant dry weight, yield, or average individual berry weight in year 2. Leaf P, K, Ca, Mg, S, and Mn concentrations, on the other hand, were lower with S fertigation than with granular S during the first year after planting, while leaf N, P, and S were lower with S fertigation the second year. The findings indicate that S fertigation can be used to reduce soil pH following planting in blueberry and therefore may be a useful practice and safer than acids to correct problems with high pH. However, it was less effective and more time consuming than applying granular S prior to planting.